FACTORS MOTIVATING CUSTOMERS Savings in banks PEOPLE IN INDONESIA UNIT PAKEM SLEMAN YOGYAKARTA - Retnawati, Eni; Kahu Lantum, MS, Drs. Alex (Management, 2010)
In taking a customer´s decision is influenced by several factors: internal factors, external factors, and decision making process. Internal factors consist of motivation, personality, self concept, and learn from the attitudes of individuals. External factors consist of culture, social class, and family. Meanwhile, decision-making process consists of problem recognition, information search, alternative evaluation, purchase decision, and purchasing behavior. Motivation is a general term used to refer to the drive (drive), desire (desire), needs (needs), desires (wishes), and other similar. There are several theories about motivation theory antaralain is content. This theory emphasizes the importance of understanding the factors that exist within the individual that caused them to behave in particular. To attract customers as much as possible in the face of competition in the banking world, various efforts have been taken by the bank, among others, by the way: Creating a wide range of products which can attract prospective customers. Provide a level of deposit rates relatively high. Providing services that best customer satisfaction and safety in saving, Giving gifts either directly or through a lottery. keyword: customer,provide,saving